Role of the Cellular Prion Protein in Oligodendrocyte Precursor Cell Proliferation and Differentiation in the Developing and Adult Mouse CNS - Bribián, Ana; Fontana, Xavier; Llorens, Franc; Gavín, Rosalina; Reina, Manuel; García-Verdugo, José Manuel; Torres, Juan María; de Castro, Fernando; Río, José Antonio del (PLOS ONE, 2012)
There are numerous studies describing the signaling mechanisms that mediate oligodendrocyte precursor cell (OPC) proliferation and differentiation, although the contribution of the cellular prion protein (PrPc) to this process remains unclear. PrPc is a glycosyl-phosphatidylinositol (GPI)-anchored glycoprotein involved in diverse cellular processes during the development and maturation of the mammalian central nervous system (CNS). Here we describe how PrPc influences oligodendrocyte proliferation in the developing and adult CNS. OPCs that lack PrPc proliferate more vigorously at the expense of a delay in differentiation, which correlates with changes in the expression of oligodendrocyte lineage markers. In addition, numerous NG2-positive cells were observed in cortical regions of adult PrPc knockout mice, although no significant changes in myelination can be seen, probably due to the death of surplus cells.